2015
DOI: 10.1038/ncomms7875
|View full text |Cite
|
Sign up to set email alerts
|

REGγ is critical for skin carcinogenesis by modulating the Wnt/β-catenin pathway

Abstract: Here we report that mice deficient for the proteasome activator, REGg, exhibit a marked resistance to TPA (12-O-tetradecanoyl-phorbol-13-acetate)-induced keratinocyte proliferation, epidermal hyperplasia and onset of papillomas compared with wild-type counterparts. Interestingly, a massive increase of REGg in skin tissues or cells resulting from TPA induces activation of p38 mitogen-activated protein kinase (MAPK/p38). Blocking p38 MAPK activation prevents REGg elevation in HaCaT cells with TPA treatment. AP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 43 publications
9
69
0
Order By: Relevance
“…This finding is in line with the critical role of β -catenin inactivation in a series of studies. 42, 43 It is also consistent with our previous study illustrating the inhibitory effect of miR-27a/PPAR γ axis in renal tubulointerstitial fibrosis in DN. 44 In glomerular mesangial cells, miR-27a has been reported to induce progression of DN by targeting PPAR γ .…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with the critical role of β -catenin inactivation in a series of studies. 42, 43 It is also consistent with our previous study illustrating the inhibitory effect of miR-27a/PPAR γ axis in renal tubulointerstitial fibrosis in DN. 44 In glomerular mesangial cells, miR-27a has been reported to induce progression of DN by targeting PPAR γ .…”
Section: Discussionsupporting
confidence: 91%
“…To evaluate the role of REGγ during melanoma progression, REGγ was silenced with specific shRNA as described in A375 and SK‐MEL‐28 human melanoma cells. We found that cell growth was significantly decreased in ShR (REGγ knockdown) cells by MTT assay (Figure A, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As GSK‐3β has been demonstrated as a target protein of REGγ‐proteasome system in our previous non‐melanoma skin cancer model, this phenomenon was investigated in melanoma cells. We found that REGγ knockdown increased the level of total GSK‐3β with concurrent decrease in β‐catenin in A375 and SK‐MEL‐28 cells (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSME3-KO mice were described previously (Li et al, 2015). All the protocols were approved by East China Normal University.…”
Section: Methodsmentioning
confidence: 99%